Non-Phenolic Linear Diarylheptanoids from Curcuma xanthorrhiza: A Novel Type of Topical Anti-Inflammatory Agents: Structure-Activity Relationship - P. Claeson (2018)
The topical anti-inflammatory activity of three nonphenolic linear 1,7-diarylheptanoids, previously isolated from a Thai medicinal plant, Curcuma xonthorrhiza (Zingiberaceae) and four new semi-synthetic derivatives of the naturally occurring compounds were assessed in the murine model of ethyl phenylpropiolate-induced ear edema. The naturally occurring compound 1E,3E,1,7-diphenylheptadien-5-one (6) exerted the most potent anti-inflammatory activity, with an ID50 value of similar magnitude to that of the reference drug oxyphenbutazone (67 vs. 46 μg|ear, respectively). None of the semi-synthetic diarylheptanoids was more active than 6. The chemical structures and pharmacological data of the natural and semi-synthetic derivatives identified a distinct structure-activity relationship. The degree of unsaturation in positions 1 and 3, and the nature of the oxygenated functional group in position 5 of the C7-chain were found to play significant roles in determining the observed in vivo activity. Based on these findings, the non-phenolic linear 1,7-diarylheptanoids are proposed to represent a novel class of topical anti-inflammatory agents.